A renal variant of Fabry disease: A case with a novel Gal A hemizygote mutation - Jorge H. Mukdsi; Silvina Gutiérrez; Belén Barrón; Pablo Novoa; Segundo Fernández; Ana B de Diller; Alicia I. Torres; Richard N Formica Jr; Marcelo Orías (Society of Diabetic Nephropathy Prevention, 2012)
Background: Fabry disease is caused by an X-linked recessive inborn error of glycosphingolipid metabolism with deficient activity of a lysosomal enzyme, alpha-galactosidase A (α-GalA). Case Presentation: A 46 year-old man with progressive kidney disease showed on kidney biopsy electron microscopic evidence of Fabry disease. The patient had no systemic manifestations of Fabry disease, despite residual α-GalA activity, therefore genetic testing was done by direct DNA sequencing, demonstrating a new GAL A gene mutation (C174G-exon 3). After three years of enzyme replacement therapy (agalsidase beta) treatment, a second biopsy was done. Although there was demonstrable clearance of intracellular inclusions, remarkable podocyte activation was evident. Conclusions: This report represents an unusual renal variant of Fabry disease and provides histologic data on long-term follow up after enzyme replacement therapy.